Black hole magnetosphere with small-scale flux tubes – II. Stability and dynamics. Issue 3 (10th June 2019) - Yuan, Yajie; Spitkovsky, Anatoly; Blandford, Roger D; Wilkins, Dan R
ABSTRACT: In some Seyfert galaxies, the hard X-rays that produce fluorescent emission lines are thought to be generated in a hot corona that is compact and located at only a few gravitational radii above the supermassive black hole. We consider the possibility that this X-ray source may be powered by small-scale magnetic flux tubes attached to the accretion disc near the black hole. We use three-dimensional, time-dependent, special relativistic, force-free simulations in a simplified setting to study the dynamics of such flux tubes as they get continuously twisted by the central compact star/black hole. We find that the dynamical evolution of the flux tubes connecting the central compact object and the accretion disc is strongly influenced by the confinement of the surrounding field. Although differential rotation between the central object and the disc tends to inflate the flux tubes, strong confinement from surrounding field quenches the formation of a jet-like outflow, as the inflated flux tube becomes kink unstable and dissipates most of the extracted rotational energy relatively close to the central object. Such a process may be able to heat up the plasma and produce strong X-ray emission. We estimate the energy dissipation rate and discuss its astrophysical implications.